Upaya Peningkatan Hasil Belajar dan Sikap Kerjasama Siswa Melalui Penerapan Discovery Learning - Dwi Cahyaningtyas; Naniek Sulistya Wardani; Narwastujati Sepharibada Yudarasa (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
This research aims to a) improve thematic learning outcomes and students' cooperative attitudes in third grades at SD Negeri Gondangan by implementing discovery learning. b) describe the steps of discovery learning that can improve thematic learning outcomes and students' cooperative attitudes. This type of research was classroom action research. The model of classroom action research used Kemmis & Mc Taggart design with using 2 cycles, then each cycle consisting of 3 stages namely, 1) action planning, 2) action implementation and observation, 3) reflection. The subjects of this study were 14 third grade students of SD Negeri Gondangan. The results of the study show that improving learning outcomes and students' cooperative attitudes in thematic learning can be pursued through proven discovery learning. This can be seen in the comparison of the percentage of completeness of student learning outcomes cycle I and cycle II, namely 64.29%: 100%. Student learning outcomes based on the minimum score of cycle I and cycle II, namely 50: 80. Student learning outcomes based on the maximum score of cycle I and cycle II of 80:100. Student learning outcomes based on the average score of cycle I and cycle II are 68.57:87.14. In addition, the comparison of the percentage of completeness of the attitude scale assessment cycle I and cycle II is 57%: 100%. It can be concluded if the classroom action research was succesfull, this is indicated by the large percentage of students who achieve completeness with KKM = 70.